Sistem Visualisasi Data Sertifikasi Karyawan Berbasis Website Menggunakan Metode Naive Bayes - Talaba, Djeliyana; Sudarsana, I Wayan; Al Fajri, Iman (Fraktal : Jurnal Matematika dan Pendidikan Matematika, 2024)
Employee certification in a company is one of the important aspects in the world of work that will show the competence and quality of an employee. However, to get the appropriate results, the company uses a support system from data analysts. This research aims to create a website-based data visualization system that can present employee certification information clearly, get the results of employee data analysis for certification decision making using the Naive Bayes method. This research was conducted in 2 stages, namely the training and testing stages using 5 attributes. Data processing was carried out using 59 training data and 59 testing data. This research produces a system that can assist in making decisions on the eligibility of employees who want to take certification using the naive bayes method and visualize it, the results obtained from the system are 10 data that are not eligible for certification with an accuracy of 96%.